2021
DOI: 10.1136/jitc-2021-002954
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species trigger metformin-dependent antitumor immunity via activation of Nrf2/mTORC1/p62 axis in tumor-infiltrating CD8T lymphocytes

Abstract: BackgroundMetformin (Met) is the first-line treatment for type 2 diabetes mellitus and plays an effective role in treating various diseases, such as cardiovascular disease, neurodegenerative disease, cancer, and aging. However, the underlying mechanism of Met-dependent antitumor immunity remains to be elucidated.MethodsMitoTEMPO, a scavenger of mitochondrial superoxide, abolished the antitumor effect of Met, but not antiprogrammed cell death (PD-1) antibody (Ab) treatment. Consequently, we studied the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 50 publications
(50 reference statements)
4
45
0
Order By: Relevance
“…Thus, active metabolism in Hot 1 tumors might be one of the reasons for T cell dysfunction via increased competition with effector T cells [ 13 ]. Therefore, targeting and controlling activated glycolysis, lipid metabolism, oxidative phosphorylation and mitochondrial function in Hot 1 tumors would be expected to improve the antitumor T cell response, and hence prognosis [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, active metabolism in Hot 1 tumors might be one of the reasons for T cell dysfunction via increased competition with effector T cells [ 13 ]. Therefore, targeting and controlling activated glycolysis, lipid metabolism, oxidative phosphorylation and mitochondrial function in Hot 1 tumors would be expected to improve the antitumor T cell response, and hence prognosis [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%
“…However, metformin may inhibit tumor cell proliferation through immune-mediated mechanisms because metformin directly improves effector T-cell function in vivo . Combining metformin with an anti-PD-1 treatment directly activates CD8 + T cells and boosts IFN-γ secretion, leading to the decreased glycolysis and OXPHOS of tumor cells compared with anti-PD-1 treatment alone ( 91 ). It is found that metformin-treated animals reduce the PD-L1 stability on cancer cells, then increase the activity of cytotoxic T lymphocytes ( 92 ).…”
Section: Targeting Metabolism and Hypoxia To Enhance Immunotherapy Re...mentioning
confidence: 99%
“…Although glycolysis predominates in the metabolic reprogramming of cancer cells, OXPHOS is also enhanced in tumor cells, and some compounds targeting OXPHOS to suppress tumors have been studied ( 178 , 179 ). An example is metformin, which could decrease cancer cell proliferation by decreasing the NAD+/NADH ratio and inhibiting aspartate production ( 180 ), and stimulates the proliferation of CD8+ TILs with the production of mitochondrial ROS in an NF-E2-related factor 2 (Nrf2)/mTORC1/p62 pathway ( 181 ). It was also reported that metformin could further improve intratumoral T-cell function and tumor clearance when combined with ICIs ( 62 , 181 , 182 ).…”
Section: Aberrant Mitochondrial Biogenesis In Cancer Cells With Immune Cells and Their Effects On The Expressions Of Immune Checkpointsmentioning
confidence: 99%
“…An example is metformin, which could decrease cancer cell proliferation by decreasing the NAD+/NADH ratio and inhibiting aspartate production ( 180 ), and stimulates the proliferation of CD8+ TILs with the production of mitochondrial ROS in an NF-E2-related factor 2 (Nrf2)/mTORC1/p62 pathway ( 181 ). It was also reported that metformin could further improve intratumoral T-cell function and tumor clearance when combined with ICIs ( 62 , 181 , 182 ). Phase II clinical trial showed metformin therapy was associated with better-than-expected OS on non-diabetic patients with advanced-stage ovarian cancer ( 183 ).…”
Section: Aberrant Mitochondrial Biogenesis In Cancer Cells With Immune Cells and Their Effects On The Expressions Of Immune Checkpointsmentioning
confidence: 99%